2012
DOI: 10.1371/journal.pone.0030310
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells (EPCs) as Gene Carrier System for Rat Model of Human Glioma

Abstract: BackgroundDue to their unique property to migrate to pathological lesions, stem cells are used as a delivery vehicle for therapeutic genes to tumors, especially for glioma. It is critically important to track the movement, localization, engraftment efficiency and functional capability or expression of transgenes of selected cell populations following transplantation. The purposes of this study were to investigate whether 1) intravenously administered, genetically transformed cord blood derived EPCs can carry h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…We found that EF1 and CMV promoters are ideal for high level expression of transgene [89]. Recently, we have determine the migration and accumulation of genetically altered EPCs where UCB derived EPCs transduced to carry human sodium iodide symporter (hNIS) gene and injected into glioma bearing rats and we observed their migration to tumor site and functional expression of transgenes [91]. These experiments clearly highlight the capability of EPCs as gene delivery vehicles.…”
Section: Multifaceted Therapeutic Applications Of Human Umbilical Cormentioning
confidence: 91%
See 1 more Smart Citation
“…We found that EF1 and CMV promoters are ideal for high level expression of transgene [89]. Recently, we have determine the migration and accumulation of genetically altered EPCs where UCB derived EPCs transduced to carry human sodium iodide symporter (hNIS) gene and injected into glioma bearing rats and we observed their migration to tumor site and functional expression of transgenes [91]. These experiments clearly highlight the capability of EPCs as gene delivery vehicles.…”
Section: Multifaceted Therapeutic Applications Of Human Umbilical Cormentioning
confidence: 91%
“…Tumor invasive properties of EPCs allow its possibility to use them as gene delivery vehicles to tumors [87–89]. EPCs based gene delivery offers several advantages over traditional gene therapy based on vectors or virus due to EPCs’ ability to cross tumor blood brain barrier (TBBB) and also their extended homing properties at the disease site [90,91]. Vascular endothelial growth factor (VEGF) gene delivery through EPCs enhances the proliferation and migration of human aortic endothelial cells following ultrasonic microbubble transfection (UMT) [92].…”
Section: Multifaceted Therapeutic Applications Of Human Umbilical Cormentioning
confidence: 99%
“…The EPCs can be used as part of a gene carrier/delivery system for glioma therapy and imaging probes. 31 Santarelli et al 32 used mouse tumor models to demonstrate that the BMderived EPCs are greatly mobilized into the bloodstream, and specifically migrate to tumor tissues.…”
Section: Tail Vein-injected Epcs Were Mainly Distributed In the Livermentioning
confidence: 99%
“…Owing to their unique property of migration to pathological lesions, stem cells are considered to be used as a delivery vehicle for therapeutic genes to tumors, especially for glioma [11 -13]. EPCs, a subpopulation of pluripotent hematopoietic stem cells (HSCs), could migrate actively to glioma [14-16], being incorporated directly in the neovasculature with high specificity [17-19].…”
Section: Introductionmentioning
confidence: 99%